V-237 AN, improved maize cultivar “Ancho Pozolero” for the region of Guerrero - Gómez-Montiel, Noel Orlando; Cantú-Almaguer, Miguel Ángel; Hernández-Galeno, César del Ángel; Vázquez Carrillo, María Gricelda; Aragón Cuevas, Flavio; Palemón Alberto, Francisco (Revista Mexicana de Ciencias Agrícolas, 2018)
A major achievement to keep the planting of native maize populations in the State of Guerrero and around the country is the improvement of landraces, aiming to decrease low agronomic and production problems. In the case of race Pozolero, the INIFAP in Guerrero has generated the open-pollinated variety V-237 AN, with agronomic traits superior to the original population, having decreased plant height and ear on 32 and 25 cm respectively, increased lodging resistance and better anchor addition, synchrony between male and female f lowering narrowed to two days, allowing a decrease in the percentage of unproductive plants (hours) in 5%. On the other hand, due to the selection method applied, gained in area of adaptation of maize to the semi-warm with intermediate elevation region from 1200 to 1800 m, with respect to the production of grain, the new variety V -237 AN outperforms grain producer Landrace 5-10%.
Keywords: Zea mays L.; landrace; wide-corn